2006
DOI: 10.1086/497529
|View full text |Cite
|
Sign up to set email alerts
|

Current Sheet Evolution in the Aftermath of a CME Event

Abstract: We report on SOHO UVCS observations of the coronal restructuring following a coronal mass ejection (CME) on 2002 November 26, at the time of a SOHO-Ulysses quadrature campaign. Starting about 1.5 hr after a CME in the northwest quadrant, UVCS began taking spectra at 1.7 R , covering emission from both cool and hot plasma. Observations continued, with occasional gaps, for more than 2 days. Emission in the 974.8 8 line of [Fe xviii], indicating temperatures above 6 ; 10 6 K, was observed throughout the campaign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
98
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 36 publications
(63 reference statements)
13
98
3
Order By: Relevance
“…Comparing it with those similar ones observed previously (Ciaravella et al 2002;Ko et al 2003;Webb et al 2003;Lin et al 2005;Bemporad et al 2006), we are able to identify this structure with the CME/flare current sheet. What is especially interesting was that a set of plasma blobs flowing in the sheet were seen between 12:18 and 12:35 UT.…”
Section: Bi-directional Reconnection Outflows Observed In a Single Eventsupporting
confidence: 78%
See 4 more Smart Citations
“…Comparing it with those similar ones observed previously (Ciaravella et al 2002;Ko et al 2003;Webb et al 2003;Lin et al 2005;Bemporad et al 2006), we are able to identify this structure with the CME/flare current sheet. What is especially interesting was that a set of plasma blobs flowing in the sheet were seen between 12:18 and 12:35 UT.…”
Section: Bi-directional Reconnection Outflows Observed In a Single Eventsupporting
confidence: 78%
“…Poletto et al (2004) extrapolated Ulysses measurements back to the Sun using the in situ measurement of the flow speed of the solar wind plasma, which gave a rough estimate of the origin time for the plasma, and yielded a positive identification of the plasma resulting from the 2002 November 26 CME by comparing features in the solar wind with phenomena directed toward Ulysses in the corona. Therefore, Bemporad et al (2006) concluded that a relation of the ICME detected by Ulyssees to the CME observed near the Sun by several other instruments could be set up, and the model shown in Fig. 2 fits the scenario manifested by this event very well.…”
Section: Identifications Of the Current Sheet In The Solar Eruptive Ementioning
confidence: 70%
See 3 more Smart Citations